Brain-Specific Increase in Leukotriene Signaling Accompanies Chronic Neuroinflammation and Cognitive Impairment in a Model of Gulf War Illness - Attaluri, Sahithi; Upadhya, Raghavendra; Kodali, Maheedhar; Madhu, Leelavathi N.; Upadhya, Dinesh; Shuai, Bing; Shetty, Ashok K. (Frontiers in Immunology, 2022)
Persistent cognitive impairment is a primary central nervous system-related symptom in veterans afflicted with chronic Gulf War Illness (GWI). Previous studies in a rat model have revealed that cognitive dysfunction in chronic GWI is associated with neuroinflammation, typified by astrocyte hypertrophy, activated microglia, and enhanced proinflammatory cytokine levels. Studies in a mouse model of GWI have also shown upregulation of several phospholipids that serve as reservoirs of arachidonic acid, a precursor of leukotrienes (LTs). However, it is unknown whether altered LT signaling is a component of chronic neuroinflammatory conditions in GWI. Therefore, this study investigated changes in LT signaling in the brain of rats displaying significant cognitive impairments six months after exposure to GWI-related chemicals and moderate stress. The concentration of cysteinyl LTs (CysLTs), LTB4, and 5-Lipoxygenase (5-LOX), the synthesizing enzyme of LTs, were evaluated. CysLT and LTB4 concentrations were elevated in the hippocampus and the cerebral cortex, along with enhanced 5-LOX expression in neurons and microglia. Such changes were also associated with increased proinflammatory cytokine levels in the hippocampus and the cerebral cortex. Enhanced CysLT and LTB4 levels in the brain could also be gleaned from their concentrations in brain-derived extracellular vesicles in the circulating blood. The circulating blood in GWI rats displayed elevated proinflammatory cytokines with no alterations in CysLT and LTB4 concentrations. The results provide new evidence that a brain-specific increase in LT signaling is another adverse alteration that potentially contributes to the maintenance of chronic neuroinflammation in GWI. Therefore, drugs capable of modulating LT signaling may reduce neuroinflammation and improve cognitive function in GWI. Additional findings demonstrate that altered LT levels in the brain could be tracked efficiently by analyzing brain-derived EVs in the circulating blood.